Congested sidewalks: The effects of the built environment on e-scooter parking compliance - Rob Hemphill; John MacArthur; Philip Longenecker; Garima Desai; Lillie Nie; Abbey Ibarra; Jennifer Dill (Journal of Transport and Land Use)
With the proliferation of electric scooters (e-scooters) in cities across the world, concerns continue to arise about their parking spots on sidewalks and other public spaces. Research has looked at e-scooter parking compliance and compared compliance to other mobility devices, but research has not yet examined the impacts of the built environment on parking compliance. Using a field observation dataset in Portland, Oregon, and novel GIS data, we attempt to understand the spatial distribution of e-scooter parking and the impact of built features on parking compliance, offering recommendations for policymakers and future research. The results of our study show that 76% of e-scooters observed fail at least one of the Portland’s parking compliance requirements and 59% fail at least two criteria. However, compliance varies spatially and by violation type, indicating that parking compliance (or non-compliance) is dependent on features of the built environment. Parking compliance is significantly higher on blocks with designated e-scooter parking than blocks without designated e-scooter parking. A statistically significant relationship is observed between the amount of legally parkable area on a city block and parking compliance. Parking compliance increases with larger percentages of legally parkable area. This finding can help policymakers prioritize dedicated e-scooter parking for blocks with limited legally parkable area.